Teacher education and the PNE: Contradictions and challenges of distance learning and valorization of the teaching profession - Carlos Eduardo Sanches; Alboni Marisa Dudeque Pianovski Vieira (Arizona State University, 2020)
The National Education Plan (Plano Nacional de Educação - PNE) established goals for valuing the teaching profession and prioritized the need for adequate training in the area of teaching practice. In this article, the evolution of teacher education by teaching stage, the effect of distance learning courses and the repercussion of this scenario on teacher appreciation and teacher social recognition are analyzed. The recent guidelines approved by the National Education Council (Conselho Nacional de Educação - CNE) for the education of teachers who will work in Basic Education is also contextualized. The research, with bibliographic and documentary character, is based on the studies of Gatti, Barreto, André, Almeida (2019), Saviani (2007, 2009), Peroni (2017), among others. The legislation from the beginning of the 21st century until 2018 is analyzed, as well as data available on the Ministry of Education (MEC) and National Institute of Educational Studies and Research Anísio Teixeira (INEP) portals. As a result, it was concluded, in this study, that the majority of teachers are graduated in distance courses in private institutions. Even so, it will not be possible to meet the PNE Goals 15 (Higher Education) and 16 (Postgraduate studies) by 2024.